1996
DOI: 10.1002/(sici)1097-4652(199602)166:2<413::aid-jcp20>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinase B is involved in the in vitro wound repair of human respiratory epithelium

Abstract: Following epithelial injury, extracellular matrix undergoes imposing remodelings. We examined the contribution of matrix metalloproteinases, gelatinases A and B, in an in vitro wound repair model of human respiratory epithelium. Confluent human surface respiratory epithelial (HSRE) cells cultured from dissociated surface cells of human nasal polyps were chemically injured. Over the next 3 to 5 days, cells migrated onto the injured area to repair the circular wound. Repair kinetics of these wounds was monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 41 publications
3
87
0
3
Order By: Relevance
“…MMPs are a family of zinc-and calcium-dependent endopeptidases capable of proteolytically degrading many of the components of the ECM (43), and TIMPs are the endogenous inhibitors of MMPs (44). In pulmonary diseases, MMPs are believed to be associated with wound repair of the human respiratory epithelium (45), while TIMPs are believed to be associated with irreversible pulmonary structure remodeling via myofibroblasts (46). The imbalance of these factors is thought to contribute to the development of interstitial lung diseases (47).…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are a family of zinc-and calcium-dependent endopeptidases capable of proteolytically degrading many of the components of the ECM (43), and TIMPs are the endogenous inhibitors of MMPs (44). In pulmonary diseases, MMPs are believed to be associated with wound repair of the human respiratory epithelium (45), while TIMPs are believed to be associated with irreversible pulmonary structure remodeling via myofibroblasts (46). The imbalance of these factors is thought to contribute to the development of interstitial lung diseases (47).…”
Section: Discussionmentioning
confidence: 99%
“…Gelatinase B (MMP-9) expression has been reported to increase in basal cells of wounded primary human bronchial epithelial cell cultures [55][56][57][58] and in distal airway cells after bleomycin injury. 89 However, similar to other groups, 59 we have previously reported that gelatinase B was not expressed in mouse tracheas and human airways at baseline or during injury 23 and once again did not find any gelatinase B expression in these current studies either in ALI cultures or in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescent staining with isotype control antibodies did not detect any nonspecific signal (data not shown). Although some groups have reported gelatinase B (MMP-9) in airway basal epithelial cells, [55][56][57][58] others have not found signal for its protein or mRNA in injured or diseased airway epithelium. 23,59 In our ALI culture repair model, gelatinase B expression was not detected by immunofluorescence in the wounded ALI culture (data not shown).…”
Section: Timp-1 and Matrilysin Co-localize At The Wound Front In Injumentioning
confidence: 99%
“…This might be achieved by lowering the O 2 concentration during resuscitation. There is therefore an ongoing debate whether to use 21% or 100% O 2 in neonatal resuscitation (3).Matrix metalloproteinases (MMPs) are involved in the pathogenesis of tissue inflammation and wound healing in lung injury (4,5). The role of oxidative stress and its toxic effects on lipids, as well as on disruption of extracellular matrix through up-regulation of MMPs, is well established (6,7).…”
mentioning
confidence: 99%